Development of an in vitro protocol for a difficult-to-propagate endemic Australian dryland sedge species Mesomelaena pseudostygia (Cyperaceae) - Lai, S.; Menon, Akshay; Turner, S.; Kodym, A.; Bunn, E. (Springer, 2014)
In vitro propagation for Mesomelaena pseudostygia a difficult-to-propagate dryland sedge species (Cyperaceae) endemic to Western Australia is described. Multiple avenues to in vitro propagation were investigated: shoot culture, organogenesis and somatic embryogenesis, with zygotic embryos as initiation material. The highest multiplication rate for shoots was 3.4 ± 1.0 after 6 wk on basal medium (1/2 strength Murashige and Skoog) with 2.5 μM kinetin and 0.5 μM 6-benzylaminopurine. Shoots achieved peak rooting (83%) following a pulse treatment on basal medium containing 10 μM indolebutyric acid and 2 μM α-naphthaleneacetic acid for 7 wk, followed by transfer to medium (without growth regulators) for a further 7 wk. Alternatively, in vitro grown shoots were pulse treated on basal medium with both 100 μM indolebutyric acid and 20 μM α-naphthaleneacetic acid for 1 wk then placed in Rockwool plugs (under propagation house conditions) for another 7 wk resulting in 63% root induction. Rooted plantlets were also successfully transferred to potting mixture either in Rockwool plugs or bare rooted and maintained in propagation house conditions with ≥95% survival after 7 wk. These results indicate that micropropagation of M. pseudostygia is feasible for small to medium scale restoration purposes. The highest frequency of callus induction was from cultured zygotic embryos on basal medium with 5 μM α-naphthaleneacetic acid, whereas 2,4-dichlorophenoxacetic acid (2 or 5 μM) produced the largest callus sizes. A low frequency of shoot regeneration occurred in zygotic callus tissues in basal medium treatments containing cytokinin (kinetin or thidiazuron at 1 μM). A small proportion (<20%) of zygotic embryo callus explants from 2,4-dichlorophenoxyacetic acid treatments were found to be embryogenic, firstly developing embryo-like structures after 2 wk on basal medium (minus plant growth hormones), that continued to develop with approximately one in twenty germinating after a further 4 wk on basal medium to form small plantlets. Further optimisation is needed to improve somatic embryogenesis efficiency for mass propagation.